Evidence for an inflationary phase transition from the LSS and CMB anisotropy data - Barriga, J; Gaztanaga, E; Santos, MG; Sarkar, S (2000)
In the light of the recent Boomerang and Maxima observations of the CMB which show an anomalously low second acoustic peak, we reexamine the prediction by Adams et al (1997) that this would be the consequence of a 'step' in the primordial spectrum induced by a spontaneous symmetry breaking phase transition during primordial inflation. We demonstrate that a deviation from scale-invariance around $k\sim0.1h$~Mpc$^{-1}$ can simultaneously explain both the feature identified earlier in the APM galaxy power spectrum as well the recent CMB anisotropy data, with a baryon density consistent with the BBN value. Such a break also allows a good fit to the data on cluster abundances even for a critical density matter-dominated universe with zero cosmological constant.